Determining the level of achievement motivation for agricultural extension agents in Baghdad Governorate (Journal of the College of Basic Education, 2022)
The research aimed to determine the achievement motivation of the agricultural extension workers in the Baghdad governorate, and to compare the areas of achievement motivation according to their rates, which include performance, perseverance, competition, and ambition.